تقييم فعالية حبيبات الزجاج النّشط حيوياً بالمشاركة مع الفيبرين الغني بالصّفيحات في معالجة الأكياس الفكّية - خليل علي; قرطة فاطمة (Latakia University Journal -Medical Sciences Series, 2016)
هدفت هذه الدراسة إلى تقييم فعالية الزجاج النشط حيوياً BAG بالمشاركة مع الفيبرين الغني بالصفيحات PRF على الشفاء العظمي بعد عملية استئصال الأكياس الفكية . تألفت عينة البحث من 20 حالة راجعت قسم جراحة الفم و الفكين في كلية طب الأسنان في جامعة تشرين، مع أكياس في الفكين يتراوح قطرها بين 0.5 – 2 سم . قسمت هذه العينة إلى مجموعتين متساويتين : المجموعة التجريبية : تألفت من 10 حالات تم تطبيق الزجاج النشط حيويا BAG بالإضافة إلى الفيبرين الغني بالصفيحات PRF. المجموعة الشاهدة : تألفت من 10 حالات تم تطبيق الفيبرين الغني بالصفيحاتPRF لوحده . تضمنت المراقبة السريرية دراسة الألم و تفزر الجرح و الإنتان خلال الأيام التالية ، و تضمنت المتابعة الشعاعية دراسة الكثافة العظمية من خلال الصور الشعاعية البانورامية الرقمية باستخدام برنامج ديجورا Digora®في مراحل مختلفة ( قبل العمل الجراحي ، بعد ثلاثة أشهر و بعد ستة أشهر من العمل الجراحي) . أظهرت النتائج وجود فروق ذات دلالة إحصائية لمشعر الألم خلال اليومين التاليين للعمل الجراحي لصالح المجموعة التجريبية، بينما لم تكن هناك فروق ذات دلالة إحصائية بالنسبة لمشعري الإنتان و تفزر الجرح خلال 48 ساعة تالية للعمل الجراحي . أظهرت دراسة مشعر الكثافة العظمية وجود فروق ذات دلالة إحصائية بعد 3 و 6 أشهر تالية للعمل الجراحي لصالح المجموعة التجريبية. أدى استخدام الزجاج النشط حيويا BAG بالمشاركة مع الفيبرين الغني بالصفيحات PRF في العيوب العظمية الناجمة عن الاستئصال الجراحي للأكياس الفكية إلى تحسين شفاء النسج الرخوة و الصلبة و زيادة الكثافة بعد ثلاثة أشهر و ستة أشهر من العمل الجراحي. The aim of this study to assesment the effect of bioactive glass (BAG) and platelet-rich fibrin (PRF) on bone healing after cystoectomy. The research sample comprised 20 cases reported to the Department of oral and maxillofacial surgery at Tishreen university , with cystic lesions in the jaws (size 0.5-2cm in diameter). This sample was divided into 2 similar groups : • The experimental group consisted of 10 cases ; was applied Platelets-rich fibrin with bioactive glass. • The control group consisted of 10 cases ; was only applied Platelets-rich fibrin without bioactive glass. The clinical observation contained studying of Pain Index , Infection Index and Wound Dehiscence Index in the days following surgery . The radiological observation contained Bone Density Measurement that had done by digital panoramic radiographs using Digora® digital program before , after 3 months and after 6 months . The present study showed that there is statistical difference between the control group and the experimental group , regarding Pain Index after the 1st and the 2nd day following surgery ,whereas there isn’t any statistical difference between the control group and the experimental group As for Infection Index and Wound Dehiscence Index after a week following surgery . As for Bone Density Measurements there are statistical differences between groups after 3 months and after 6 months following surgery for the experimental group . Using bioactive glass (BAG) and platelet-rich fibrin (PRF) in Bony defects following Cystoectomy improves the healing of hard and soft tissues , and increases bone density after 3 and 6 months .